The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3171/2017.3.jns162532
|View full text |Cite
|
Sign up to set email alerts
|

Impact of 2-staged stereotactic radiosurgery for treatment of brain metastases ≥ 2 cm

Abstract: OBJECTIVE Stereotactic radiosurgery (SRS) is the primary modality for treating brain metastases. However, effective radiosurgical control of brain metastases ≥ 2 cm in maximum diameter remains challenging and is associated with suboptimal local control (LC) rates of 37%-62% and an increased risk of treatment-related toxicity. To enhance LC while limiting adverse effects (AEs) of radiation in these patients, a dose-dense treatment regimen using 2-staged SRS (2-SSRS) was used. The objective of this study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
72
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 74 publications
0
72
0
2
Order By: Relevance
“…As our main goal was to avoid surgery in symptomatic patients, we felt that Infini would be more suitable for obtaining a quicker tumor response that hopefully traduced in faster neurological improvement. Further studies are needed to compare multifraction LINAC versus multifraction Gamma Knife and the results provided by two-or three-session Gamma Knife in the treatment of large brain metastases [18][19][20]22,23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As our main goal was to avoid surgery in symptomatic patients, we felt that Infini would be more suitable for obtaining a quicker tumor response that hopefully traduced in faster neurological improvement. Further studies are needed to compare multifraction LINAC versus multifraction Gamma Knife and the results provided by two-or three-session Gamma Knife in the treatment of large brain metastases [18][19][20]22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Radiosurgery apparently enhances the effects of low-dose steroids (e.g., 0.5 mg dexamethasone), resulting in rapid patient improvement. Our neoadjuvant radiosurgery protocol was replaced by the present study of two-session radiosurgery, inspired by staged radiosurgery schemes described by others, but with the hope to benefit not only those unsuitable for surgery, but rather those who could be operated by current recommendations standards [22][23]. It was exactly this group of patients for whom we sought to provide an apparent non-inferior, safe, effective, noninvasive alternative means of radiosurgery for rapid tumor response and control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The local recurrence rates in these studies ranged from 12.1% to 15.0% and complication incidences from 1.9% to 6.4%, results very similar to those obtained with 3-st-GK-Tx. 1,2,5 The next question is whether 3-st-GK-Tx or 2-st-GK-Tx is the better option in terms of patient outcomes. Very recently, Serizawa et al reported a multi-institutional retrospective study designed to compare the treatment results of these 2 protocols (i.e., 3-stage or 2-stage treatment).…”
Section: Discussionmentioning
confidence: 99%
“…19,20 In contrast, radiosurgeons performing Gamma Knife therapy at the Cleveland Clinic use 2-stage radiosurgery (2 doses of 15 Gy, or 18 Gy then 12 Gy administered 1 month apart), and Asher et al and Angelov et al have described the successful use of lower-dose GKSRS as neoadjuvant radiosurgery prior to resection. 1,3 As an alternative to Asher et al's protocol, the Cleveland Clinic has an in-house protocol with dose escalation for neoadjuvant radiosurgery. This latter technique allows for easier GKSRS planning because the margins are better defined, and preliminary data suggest that it also decreases the rate of leptomeningeal spread of the cancer at the time of surgery.…”
Section: Hypofractionationmentioning
confidence: 99%